2001
DOI: 10.1034/j.1600-0684.2001.d01-56.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of virus load parameters and CD8 T‐cell suppressive capacity in two SIVcpz‐infected chimpanzees

Abstract: In a longitudinal study we address the hypothesis that resis tance to disease progression in lentivirus-infected chimpanzees is related to potent non-cytotoxic suppression of virus replication. In a long-term follow-up, the viral suppressive capacity in two simian immunodeficiency virus (SIV)cpz-infected chimpanzees was correlated with two polymerase chain reaction (PCR)- and two culture-based virus load measurements. In both animals, quantitative virus isolation (QVI) tended to decline slowly, whereas in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…What insight we do have, by necessity, has come from laboratory analyses of SIVcpz-infected captive chimpanzees and ex vivo analyses of their viruses and lymphoreticular tissues. For example, studies of several SIVcpz isolates indicate that, like HIV-1, they use CD4 and CCR5 as their main receptor and coreceptor for entry into target cells (10,50,58). For reasons that remain to be explained, it appears that chimpanzee peripheral blood mononuclear cells (PBMCs) are considerably less susceptible to SIVcpz (and HIV-1) infection in vitro than are human PBMCs (8,57).…”
Section: The Natural History Of Sivcpz Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…What insight we do have, by necessity, has come from laboratory analyses of SIVcpz-infected captive chimpanzees and ex vivo analyses of their viruses and lymphoreticular tissues. For example, studies of several SIVcpz isolates indicate that, like HIV-1, they use CD4 and CCR5 as their main receptor and coreceptor for entry into target cells (10,50,58). For reasons that remain to be explained, it appears that chimpanzee peripheral blood mononuclear cells (PBMCs) are considerably less susceptible to SIVcpz (and HIV-1) infection in vitro than are human PBMCs (8,57).…”
Section: The Natural History Of Sivcpz Infectionmentioning
confidence: 99%
“…Even in captive chimpanzees, only seven naturally infected individuals have been identified (17,24,51,63,64), and among these, only one (Noah) has been subjected to virological and immunological analyses (13,40,41,54,(56)(57)(58). Observational studies of both captive and wildliving apes seem to suggest that SIVcpz-infected chimpanzees do not become noticeably immunodeficient or succumb prematurely to opportunistic infections or neoplasms, although an obvious caveat here is that it is difficult in field studies to distinguish between these and other natural causes of death.…”
Section: The Natural History Of Sivcpz Infectionmentioning
confidence: 99%
“…There are a few possible explanations to this puzzle. For example, chimps in the wild carry SIVcpz and show a low to moderate viral load yet appear to be immune to this lentivirus against the development of AIDS (Ondoa et al 2001). Similarly, several African non-human primates carry various versions of SIVs but remain unaffected by them.…”
Section: Role Of Sirnas In Development Of Hiv-1 Vaccinementioning
confidence: 99%
“…Previously, Kestens et al observed a fluctuating pattern with the measurement of virus titers in plasma varying from undetected to 1,000 tissue culture infectious doses/ml (49). From the end of 1997 to 2001 (i.e., dates after our panel), Ondoa et al quantified viral RNA from Ch-No plasma samples with a specific in-house assay, and the values varied from 3.93 to 5.80 log 10 copies/ml (50,51), in the range of our viral loads. Therefore, despite the high genetic distances between SIVcpz strains, our assay was able to detect and quantify the SIVcpzPtt and SIVcpzPts RNA from chimpanzee plasma samples.…”
Section: Reproducibility and Variations Between And Within Runsmentioning
confidence: 99%